Formulation of Blended Learning Lecture Activities Based on the Assessment of Lecturers and Students of the Economic Education Study Program FKIP Universitas Riau - Adinda Nurul Izzah Salma; Gani Haryana; Almasdi Syahza (CV. Rayyan Dwi Bharata, 2023)
This study aims to formulate blended learning lecture activities based on lecturer assessments and student assessments of the Economics Education Study Program, FKIP, University of Riau. The background of this research is the use of blended learning models that will be used in lecture activities. This study uses a type of quantitative research. This research was conducted at the Economics Education Study Program, FKIP, University of Riau. The size of the population is 92 respondents, with a sample of 19 lecturers and 73 students of the Economics Education Study Program, FKIP, University of Riau. The data collection technique was carried out by distributing questionnaires. The data analysis technique used is descriptive analysis. The results of the study show that face-to-face lecture activities and structured assignment lecture activities are effectively formulated into blended learning while independent learning lecture activities cannot be formulated into blended learning, because the results of lecturer and student assessments show differences in assessment of independent learning lecture activities.